2021
DOI: 10.1126/sciadv.abd6449
|View full text |Cite
|
Sign up to set email alerts
|

Adipose saturation reduces lipotoxic systemic inflammation and explains the obesity paradox

Abstract: Obesity sometimes seems protective in disease. This obesity paradox is predominantly described in reports from the Western Hemisphere during acute illnesses. Since adipose triglyceride composition corresponds to long-term dietary patterns, we performed a meta-analysis modeling the effect of obesity on severity of acute pancreatitis, in the context of dietary patterns of the countries from which the studies originated. Increased severity was noted in leaner populations with a higher proportion of unsaturated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 84 publications
(167 reference statements)
0
50
0
Order By: Relevance
“… 12 , 13 , 14 This process, if uncontrolled, generates an overwhelmed amount of nonesterified fatty acids (NEFAs), which in turn aggravate the damage to pancreatic acinar cells and even lead to organ failure. 12 , 13 , 15 The liver serves as a metabolic hub responsible for maintaining the homeostasis of fatty acids, glucose, and amino acids. 16 Fatty acid β-oxidation (FAO) is a major catabolic process that degrades long-chain (LC) acyl-CoA to acetyl-CoA, 17 which then enters the tricarboxylic acid (TCA) cycle or ketogenesis process for energy production.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 , 14 This process, if uncontrolled, generates an overwhelmed amount of nonesterified fatty acids (NEFAs), which in turn aggravate the damage to pancreatic acinar cells and even lead to organ failure. 12 , 13 , 15 The liver serves as a metabolic hub responsible for maintaining the homeostasis of fatty acids, glucose, and amino acids. 16 Fatty acid β-oxidation (FAO) is a major catabolic process that degrades long-chain (LC) acyl-CoA to acetyl-CoA, 17 which then enters the tricarboxylic acid (TCA) cycle or ketogenesis process for energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting the obesity paradox in trauma proposed several mechanisms to explain the counterintuitive relation between higher than normal BMI and improved survival. These include: 1. upregulation of cytokines produced by adipose tissue, especially leptin, which alter susceptibility to infection and toxicity of proinflammatory stimuli [ 30 ]; 2. visceral triglyceride saturation interferes with triglyceride interaction and lipolysis, reducing lipotoxic systemic injury and organ failure [ 31 ]; 3. presence of high nutritional reserves enable tolerance to malnutrition states associated with ICU admission [ 29 , 32 ]; 4. shortcomings of BMI in differentiating adiposity from muscle mass, highlighted by studies that found that the obesity paradox disappeared when using alternative adiposity measures (like waist-to-hip ratio) [ 33 , 34 ]. We hypothesize that studies reporting obesity paradox in trauma missed adjusting for an objective and accurate measure comparing injury grade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, especially in AP, increased lipolysis seems to account for adverse outcomes by setting free unsaturated fatty acids that potentiate necrosis and worsen local and systemic inflammation [66] mediated by a storm of cytokines, predominantly IL-6, IL-8, and IL-10 [67]. Diet-induced visceral fat unsaturation has therefore recently been suggested as a driver of AP severity and potential explanation for an obesity paradox [68]. By contrast, in CP, intra-pancreatic adipocytes are surrounded by fibrotic tissue, which limits lipolysis and, thus, ameliorates severity of acute exacerbations in CP [69].…”
Section: Mechanismsmentioning
confidence: 99%